Proteome changes of dairy calves rumen epithelium from birth to postweaning - Zheng, Kaizhi; Wu, Jianliang; Ullah, Saif; Cao, Yang; Jiang, Yongqing; Huang, Xin; Jiang, Junfang (Frontiers in Genetics, 2023)
Background: Rumen epithelium plays a central role in absorbing, transporting, and metabolizing of short-chain fatty acids. For dairy calves, the growth of rumen papillae greatly enhances the rumen surface area to absorb nutrients. However, the molecular mechanism underlying dairy calves rumen postnatal development remains rarely understood. Results: Here, we firstly describe the histological change of rumen epithelium from birth to day 90 of age. Then, a shotgun approach and bioinformatics analyses were used to investigate and compare proteomic profiles of Holstein calve rumen epithelium on day 0, 30, 60 and 90 of age. A total of 4372 proteins were identified, in which we found 852, 342, 164 and 95 differentially expressed proteins (DEPs) between D0 and D30, between D30 and D60, between D60 and D90, respectively. Finally, Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses were performed to provide a comprehensive proteomic landscape of dairy calves rumen development at tissue level. Conclusion: To conclude, our data indicated that keratinocyte differentiation, mitochondrion formation, the establishment of urea transport and innate immune system play central roles during rumen epithelium development. Tetrahydrobiopterin (BH4) presents an important role in rumen epithelial keratinization. The biological processes of BH4 biosynthesis and molecular function of nicotinamide adenine dinucleotide phosphate (NADP) binding participate in mitochondrial cristae formation. The proposed datasets provide a useful basis for future studies to better comprehend dairy calves rumen epithelial development.